Pengaruh Awareness Kelengkapan Produk Dan Kualitas Produk Terhadap Keputusan Pembelian Pada Toko Grosir Kembar Desa Pengarungan Kec.Torgamba - Mila Utama Ari Marpaung; Novrihan Leily; Fadzil Hanafi Asnora (Universitas Labuhanbatu, 2021)
This study aims to examine the effect of Awareness, completeness of goods and quality of goods on purchasing decisions at the Twin wholesale stores of Pengarungan Village, Torgamba District, South Labuhanbatu Regency. Data collection was carried out by distributing questionnaires and distributed to 60 research samples, namely customers of Twin grocery stores. Data analysis in this study using the help of SPSS version 20. Data testing techniques conducted in this study include validity and reliability test, classical assumption test, multiple linear regression analysis, and partial and simultaneous testing. The results of the analysis showed that awareness has a positive effect on purchasing decisions it can be seen from the value of t count > t table (2.933>2.002), awareness has a positive effect on purchasing decisions it can be seen from the value of t count > t table (2.466>2.002), awareness has a positive effect on purchasing decisions it can be seen from the value of t count > t table (5.092>2.002), Awareness, completeness of goods, and quality of goods have a positive effect on purchasing decisions it can be seen from the value of F count > F table (11,223>2,77).